Re/presenting Class : Essays in Postmodern Marxism - Wolff, Richard D.; Resnick, Stephen A.; Gibson-Graham, J. K. (Book collections on Project MUSE., 2001)
Twelve theoretical and historical essays emanate from a novel, shared poststructuralist conception of political economy.